2009
DOI: 10.1016/j.jacc.2009.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Oxidized Phospholipids and Biomarkers of Oxidized Low-Density Lipoprotein With Cardiovascular Risk Factors, Inflammatory Biomarkers, and Effect of Statin Therapy in Patients With Acute Coronary Syndromes

Abstract: In patients with ACS, baseline levels of oxidative biomarkers varied according to specific CVD risk factors and were largely independent of inflammatory biomarkers. Atorvastatin uniformly increased OxPL/apoB levels in all subgroups studied. Future studies are warranted to assess whether the increase in OxPL/apoB levels reflects the benefit of effective therapeutic interventions and prediction of new CVD events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 48 publications
2
45
2
4
Order By: Relevance
“…Although it is not possible to ascribe a causal association in this relationship, one may speculate that patients with high baseline IgM, perhaps mediated through genetic or other factors, may be protected through undefi ned mechanisms from developing modifi able cardiovascular risk factors. This is consistent with prior data showing that IgM AA are higher in patients considered at lower cardiovascular risk, such as women, nonsmokers, and younger subjects, and are decreased in men, elderly subjects, diabetics, and patients with elevated LDL-C ( 8,34,36,37 ). Alternatively, it is also possible that some patients consume such preformed antibodies as atherosclerosis develops, which are ultimately cleared leading to lower plasma levels.…”
Section: Discussionsupporting
confidence: 91%
“…Although it is not possible to ascribe a causal association in this relationship, one may speculate that patients with high baseline IgM, perhaps mediated through genetic or other factors, may be protected through undefi ned mechanisms from developing modifi able cardiovascular risk factors. This is consistent with prior data showing that IgM AA are higher in patients considered at lower cardiovascular risk, such as women, nonsmokers, and younger subjects, and are decreased in men, elderly subjects, diabetics, and patients with elevated LDL-C ( 8,34,36,37 ). Alternatively, it is also possible that some patients consume such preformed antibodies as atherosclerosis develops, which are ultimately cleared leading to lower plasma levels.…”
Section: Discussionsupporting
confidence: 91%
“…An inverse association was also noted with Lp(a) and triglycerides, which has been noted previously. 25 Finally, although the prevalence of diabetes mellitus was not known in this study, there was a clear linear trend of increasing hemoglobin A1c with Lp(a), but no clear association with fasting glucose or insulin. These data tend to go against the several studies showing a higher rate of incident diabetes mellitus with very low Lp(a) (1-4 mg/dL), but the data likely reflect the reality of the complexities of studying patients who are potentially on treatment versus the community cohorts.…”
Section: Downloaded Fromcontrasting
confidence: 55%
“…Although the mechanistic underpinnings of these changes cannot be determined from these studies, in composite they suggest that increases in plasma OxPL/apoB in response to therapeutic measures, perhaps including diet, may refl ect a benefi cial response within the artery wall leading to reduced OxPL content. In support of improved vascular health, a recent analysis from the MIRACL trial showed that individuals with the largest increases in OxPL/apoB were those who were felt to benefi t the most from statins, such as younger patients with fewest risk factors ( 44 ). Clinical studies are underway to evaluate whether increases in OxPL/apoB in response to statins predict improved clinical outcomes.…”
Section: Downloaded Frommentioning
confidence: 99%